The Role of Dehumanization in the Incidence of Spouse Abuse from the Perspective of Female Victims of Domestic Violence: A Qualitative Study - Homa Shahbazi; Mansoureh-sadat Sadeghi; Leili Panaghi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Dehumanization is denial of one's humanity and is one of the fundamentals in interpersonal and intergroup violence as known in previous studies. The role of dehumanization in previous studies was limited to sexual violence and violence against women out of intimate relationships. Therefore this article aims to examine the role of dehumanization in domestic violence. Material and methods: This study was a qualitative grounded theory research and sampling was conducted in two stages. In the fist phase 120 women were selected through convenience sampling method in different areas of Tehran in parks, mosques, etc. The subjects were asked to complete the conflct tactics scale (CTS2). 60 out of 120 women who experienced violence and their score in (CTS2) was higher than the twentyfith percentile were chosen. In the second stage, 60 people were selected for in-depth interviews through theoretical sampling. Data in this research reached theoretical saturation with 10 participants. Data were analyzed through Strauss and Corbin method. Results: Data analysis revealed that dehumanization in the study was observed in the two main categories of objectifiation which contains sub-categories of worthlessness, incontinence, the low ability to understand and emotionlessness, and animalization including sub-categories of the low ability to understand, impulsiveness and irrationality. It was also found that as a core category, female victims of domestic violence consider dehumanization as a factor of spouse abuse. Conclusion: The fidings of this study showed that female victims of domestic violence, dehumanization in two forms objectifiation and animalization is involved with spouse abuse. Accordingly the moderator dehumanization methods can be used to reduce the incidence of spouse abuse.